Prevalence and Progression of Gingivitis in Domestic Cats in Subtropical Mexico - Ana G. Villegas-Ferré; Víctor Martínez-Aguilar; Samantha Valencia-Arjona; Eduardo Gutiérrez-Blanco; Matilde Jiménez-Coello; José C. Segura-Correa; Antonio Ortega-Pacheco (Veterinary Medicine International)
With the objective to characterize the gingival index (GI) and its progression, 218 domestic cats in a subtropical region of Mexico were studied. All teeth of each cat were examined with a periodontal probe to determine the GI; in addition, the absence of teeth was recorded. Six months later, the teeth of the 38 cats were again examined to assess any progression of the GI and loss of teeth. From the 218 cats, 33.0% of them develop some degree of gingival inflammation; from those, 61.5% were classified as GI 1. Age, sex, and neutered status were associated with tooth affections. Missed teeth were observed in 35% of the cats, particularly for molars 109 and 209 in both sexes. After six months, the number of teeth with GI 1 decreased to 20%. The gingival problems in cats have not been well studied, particularly at the speed they progress and how this can affect the loss of teeth; under the conditions of this study, a high frequency of gingival inflammation even at early age was demonstrated, with a rapid tooth loss. Although young males were more prone to develop gingivitis, females tend to loss more teeth. Non-neutered cats tended to develop more dental affections.